Kontribusi motivasi berdasarkan latar belakang sekolah terhadap prestasi belajar mahasiswa - Witri Nur Anisa; Ratna Rustina (Program Studi Pendidikan Matematika, FKIP, Universitas Siliwangi, Tasikmalaya, 2018)
This study aims to determine the contribution of learning motivation of students by school background on student achievement; Motivation to learn students graduate high school on student achievement; The motivation of student learning vocational graduates on student achievement. The learning achievement in the subjects studied Calculus 3. Before the questionnaire given to students with a background in high school and vocational school, the questionnaire beforehand on the validity and reliability. The study population was all students of mathematics education class of 2014/2015 which followed Calculus 3. Samples were taken vocational school graduates and high school graduates. The method used is multiple linear regression. Results obtained by analysis that there is no contribution of motivation to learn by school background on student achievement; Student learning motivation of high school graduates do not contribute to the achievement of students; Motivation to learn student vocational school graduates do not contribute to the achievement of students. Keywords: Motivation, Background School, Learning Achievement.